Peningkatan Kemampuan Membaca Al Quran Santri TPQ Al Azhar dengan Bimbingan Ilmu Tajwid Di Desa Bakan Kecamatan Janapria Kabupaten Lombok Tengah - Husaen Sudrajat; Syamsul Hadi; Hadlun; Ala Purnawati; M. Kamari; Intoriqatul Khairiyah; Fathurrahman; Zainal Arifin; Zainal Abidin; Rabiatul Adawiyah; Martini; Nurin Kumala Dewi; Khairul Muzakki; Muhammad Aminudin; Nisrokyah (STAI Al-Amin Gersik Kediri Lombok Barat-NTB, 2024)
This activity to improve the ability to read the Qur'an at TPQ Al Azhar students is one of several activities that have been compiled by friends of the STAI Al Amin KKN group in Bakan Village by looking at the state of the level of understanding about reading the Qur'an which is mostly lacking so that on that basis friends of the STAI Al Amin KKN group are enthusiastic to realize it and are supported by the institution, Of course, the hope and desire of a program like this for students or female students can add insight into understanding knowledge about good and correct procedures in reading the Qur'an, and gratitude and enthusiasm in teaching provide a little understanding, students increase understanding and there are changes both in letter recognition, letter makhorijul and reading law in the science of tajweed, and can also help TPQ caregivers in educating / teaching students to be more like before.